Critical heat flux enhancement in pool boiling through increased rewetting on nanopillar array surfaces - Nguyen, Thien-Binh (2018)
Boiling is a key heat transfer process for a variety of power generation and thermal management technologies. We show that nanopillar arrays fabricated on a substrate enhance both the critical heat flux (CHF) and the critical temperature at CHF of the substrate and thus, effectively increase the limit of boiling before the boiling crisis is triggered. We reveal that the enhancement in both the CHF and the critical temperature results from an intensified rewetting process which increases with the height of nanopillars. We develop a predictive model based on experimental measurements of rewetting velocity to predict the enhancement in CHF and critical temperature of the nanopillar substrates. This model is critical for understanding how to control boiling enhancement and designing various nanostructured surfaces into specific applications.